Uji Efektivitas Ekstrak Etanol Daun Jarak Pagar (Jatropha curcas L.) dalam Menurunkan Kadar Gula Darah pada Mencit (Mus musculus) yang Diinduksi Glukosa Monohidrat - Nadira Aisyah Lubis; Erida Novriani; Finna Piska (Lembaga Pengembangan Kinerja Dosen, 2026)
Diabetes mellitus is a chronic metabolic disorder with an increasing global prevalence, emphasizing the need for safe, effective, and affordable alternative therapies. This study aimed to evaluate the antidiabetic potential of ethanol extract from physic nut leaves (Jatropha curcas L.) in reducing blood glucose levels in glucose monohydrate–induced mice (Mus musculus). An experimental design was applied using 25 male mice divided into five groups: a negative control group receiving Na-CMC, a positive control group treated with glibenclamide (5 mg), and three treatment groups administered ethanol extract doses of 21.8 mg/25 g body weight, 43.7 mg/25 g body weight, and 65.6 mg/25 g body weight. Blood glucose levels were measured to assess the hypoglycemic effect of each treatment. The results showed that the ethanol extract of Jatropha curcas leaves significantly reduced blood glucose levels compared to the control groups (p < 0.05). The highest dose, 65.6 mg/25 g body weight, demonstrated the greatest reduction in blood glucose levels. These findings suggest that ethanol extract of physic nut leaves has promising potential as a natural antidiabetic agent and may serve as an alternative therapeutic option for diabetes management.